A novel stepwise method to predict ultimate strength reduction in offshore structures with pitting corrosion. (19th August 2015) - Rahmdel, Sajad; Kim, Kwanghoon; Kim, Sangjin; Park, Seonghun
Corrosion is a factor that decreases the ultimate strength of a structure, which can lead to structural failure in an aged structure. This study proposes a reliable method to predict the ultimate strength reduction caused by pitting corrosion of a structure at various ages. Hence, the objectives of this study are as follows: (1) finding relationship between the ultimate strength reduction and pit depth and (2) finding relationship between the ultimate strength reduction and the age of structure. The presented method has six steps and was assessed by applying it to the simplified example of a thin-plate panel structure. The ultimate strengths of the panel with different pit depths were calculated using finite element analysis. The effects of material and geometric nonlinearities as well as the initial imperfections and buckling were also considered. A linear regression model, representing the relationship between the ultimate strength reduction and pit depth, was then developed. Furthermore, using the experimental data, the weighted mean value of ultimate strength reduction was acquired for different age groups of the panel. The introduced stepwise approach contemplates the nonlinearity of pitting corrosion with time by considering the experimental data. As corroborated by the successful application of the presented methodology, this method is more accurate, compared to the accepted practices available in the literature.